Investigations Into Solvate forms of Naloxone using Solid-State NMR and Simulations - Mitchell-Thurston, Charles (2024)
The aim of this work is to investigate solvate forms of a pharmaceutical compound using solid-state nuclear magnetic resonance (NMR) spectroscopy to be able to differentiate them and provide structural insight, such as the change in orientation of an aliphatic chain. This was done by a combination of two approaches, one using experimental techniques and the other using simulations. Naloxone was chosen as the model compound because of its pharmaceutical importance, as well as the fact that it possesses multiple solvate forms. For all three of the available forms of naloxone, both proton and carbon-13 NMR experiments were employed.